2017
DOI: 10.1007/s00259-017-3663-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled pertuzumab for imaging of human epidermal growth factor receptor 2 expression in ovarian cancer

Abstract: Purpose Human epidermal growth factor receptor 2 (HER2) is overexpressed in over 30% of ovarian cancer cases, playing essential roles in tumorigenesis and metastasis. Non-invasive imaging of HER2 is of great interest for physicians to better detect and monitor the progression of ovarian cancer. In this study, HER2 was assessed as a biomarker for ovarian cancer imaging using 64Cu-labeled pertuzumab for immunoPET imaging. Methods HER2 expression and binding were examined in three ovarian cancer cell lines (SKO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Radiolabeled trastuzumab, 89 Zr-trastuzumab, has demonstrated HER2 specific uptake in patients with metastatic breast cancer (26). Similarly, 89 Zrpertuzumab, another HER2 targeted antibody that inhibits dimerization of HER2, has shown promise in detecting HER2 positive tumors in preclinical models and in patients with metastatic disease (28)(29)(30). The optimal image contrast times for those intact antibodies are in days, which could potentially limit their routine use in the clinic.…”
Section: Her2mentioning
confidence: 99%
“…Radiolabeled trastuzumab, 89 Zr-trastuzumab, has demonstrated HER2 specific uptake in patients with metastatic breast cancer (26). Similarly, 89 Zrpertuzumab, another HER2 targeted antibody that inhibits dimerization of HER2, has shown promise in detecting HER2 positive tumors in preclinical models and in patients with metastatic disease (28)(29)(30). The optimal image contrast times for those intact antibodies are in days, which could potentially limit their routine use in the clinic.…”
Section: Her2mentioning
confidence: 99%
“…89 Zr-labeled pertuzumab ( 89 Zr-pertuzumab) has been used to detect HER2-positive breast cancer in small human cohorts [42,43] and to delineate tumors and show treatment effects from trastuzumab-emtansine (T-DM1) in HER2-positive breast cancer xenografts [44]. Similarly, PET-CT with radiolabeled pertuzumab ( 64 Cu-NOTA-pertuzumab) was used for non-invasive detection and monitoring of HER2 tumor expression, enabling the detection of primary tumors and peritoneal metastases in both subcutaneous and orthotopic models of ovarian cancer [45].…”
Section: Radioligands For Visualization Of Target-specific Expressionmentioning
confidence: 99%
“…High specificity to HER2 expression and delineation of tumor and metastases in orthotopic and subcutaneous ovarian cancer xenografts [45].…”
Section: Radioligands For Visualization Of Target-specific Expressionmentioning
confidence: 99%
“…Non-invasive imaging of HER2 expression can allow physicians to monitor HER2-directed therapies in patients and can also be of assistance in patient stratification. Jiang et al [ 16 ] showed the usefulness of 64 Cu-labeled pertuzumab for in vivo imaging of HER2-positive ovarian cancer. In this study 64 Cu-NOTA-pertuzumab showed high specificity in an ovarian cancer cell line with high HER2 expression.…”
Section: Basic and Translational Molecular Imagingmentioning
confidence: 99%